Üble Dinge: Materialität und Fetischismus in der Prosa Paulus Hochgatterers - Oberreither, Bernhard (2022)
Bernhard Oberreither analyzes in the context of historical and contemporary fetish discourses how supposedly innocent things often turn out to be the key to the enigmatic structure of Paulus Hochgatterer's texts, and how his texts can be read at the same time as a highly reflected commentary on the always precarious, suspicious, sometimes »corrupt« (Hartmut Böhme) relationship of man to his things.